The effects of e-payment system on the efficiency of banks in Nigeria - Josephine, Chiejina Ofure (International research journal of management, IT and social sciences, 2021)
This study examines the effect of the e-payment system on the efficiency of banks in Nigeria. The specific objective of the study is to examine the impact of e- payments systems on economic growth in Nigeria to determine the implication of mobile payment on the efficiency of Nigerian banks, to identify the significance of Automated Teller Machine on the efficiency of Nigeria banks, and to determine the effect of POS on the efficiency Nigerian banks, collating data of e-payment statistics from Central Bank of Nigeria from the year 2012 to 2016. A linear regression analysis was adopted for this study using SPSS to carry out the analysis, to obtain the P-Value significance which is given at a significance level of 0.05. The result of the analysis obtained a P-Value significance of 0.333 which connotes that there is no significant effect of the e-payment system on the efficiency of banking in Nigeria. The study recommended that banks and other financial institutions should intensity efforts in mounting other e-payment channels to promote trade and commerce in Nigeria and the Central Bank of Nigeria should embark on an intensive campaign for complete adoption of e- payments products especially at the grassroots.